PENGARUH KUALITAS PRODUK, ULASAN PRODUK DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE DI KOTA BATAM - Capriati, Feronica; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2024)
The rapid advancement of internet technology has had a profound impact on businesses, particularly in termsof the convenience of online shopping. However, various challenges related to product quality, reviews, andtrust have emerged in this context. This research aimed to examine the influence of product quality, reviews,and trust on purchasing decisions within Shopee, an online marketplace. The researchers employed aquantitative research method, specifically an inferential approach, to analyze the relationship between variablesthrough hypothesis testing. A total of 204 respondents participated in the study, and data was collected throughonline questionnaires employing a Likert scale. The analysis method used is multiple linear regression. Fromthe test results, the t value of the product quality variable countsvariable X1 is 5.188 > t table (1.972) or thesignificance value of the motivation variable is 0.000 < 0.05, so the hypothesis is accepted. The findings revealeda positive and significant impact of product quality, product reviews, and trust on purchasing decisions withinShopee in Batam City